(untitled) (Journal on studies and research of academic knowledge, 2016)
The research work was carried out with the objective of evaluating the effect of nitrogen fertilization and three planting densities on maize yield in San Juan del Paraná - Itapúa, the experimental design used was divided plots arranged in complete blocks Random with three repetitions. The experiment was carried out from January to June 2015. The treatments consisted of the application of different doses of nitrogen (N): 0 kg ha-1, 80 kg.ha-1 and 150 kg ha-1, the different doses Of N were considered subplots; The densities studied were: 35 thousand/plan.ha-1, 55 thousand/plan.ha-1 and 75 thousand/plan.ha-1, as the main plot the different seed densities evaluated were considered. Significant differences were obtained in the grain yield and weight of 100 grains, the highest yield was obtained with the combination of 150 kg ha-1 and 55 thousand/pl.ha-1. Nitrogen and the different planting densities are among others factors that have a high influence on maize production.